ANALISIS WASTE MATERIAL DENGAN PENERAPAN LEAN CONSTRUCTION - Risky Irianto Girik Allo; Adwitya Bhaskara (Jurnal Teknik Sipil, 2022)
Waste material affects project implementation. In addition, it also affects the productivity of the project as well as costs and time. Based on this, good management is needed in handling and minimizing the occurrence of material waste. Lean Construction is one approach that can be used to handle and minimize this occurrence. This study aims to determine the most dominant waste material indicators that cause material waste, determine the estimated costs resulting from material waste and total cost estimates until the observed work is completed, determine the most dominant type of material that causes material waste and determine the percentage of Lean Construction implementation. The case study of this research was conducted on the Karangsambung Indonesia Geodiversity Area Facility Development Project Package 2. The Bayes theorem method was used to determine the most dominant indicator of material waste that causes material waste to occur. Pareto diagrams are used to determine the most dominant type of material that causes material waste. The data from this study were obtained by conducting interviews, observations and filling out the waste material questionnaire and the Lean Construction application questionnaire. The conclusion of this study is that the most dominant indicators that cause material waste are Defect and Waiting with a confidence value of 100% each. The estimated cost obtained during the 2-week observation is Rp. 10,440,859.91 and the estimated cost until the work is completed is Rp. 26,102,149,77. The most dominant type of material that causes material waste is deformed reinforcement Ø22 (Rp. 4,436,673.32), deformed reinforcement Ø 19 (Rp. 2,051,606 ,29) and threaded reinforcement Ø 16 (Rp. 1,387,546,88). The percentage of Lean Construction implementation obtained is 98.94%.